Multiple breath washout in primary ciliary dyskinesia: a systematic review of the literature - Andreas M. Matthaiou; Alexandra Demetropoulou; Panayiotis Kouis; Konstantinos Douros; Panayiotis Yiallouros; Pinelopi Anagnostopoulou (European Respiratory Review, 2025)
Primary ciliary dyskinesia (PCD) is a heterogeneous multiorgan genetic disease characterised by motile cilia impairment that primarily affects the respiratory system. Multiple breath washout (MBW) is an emerging pulmonary function test. Its main outcome, the lung clearance index (LCI), is a valuable sensitive measure in obstructive lung disease, especially in cystic fibrosis. The potential value of MBW as a monitoring tool for patients with PCD is not well known. This systematic review summarises all articles published by the end of 2022 reporting MBW data in patients with PCD and compares MBW parameters to spirometry and chest imaging findings. We searched PubMed, Embase and Scopus for original studies with MBW measurements in patients with PCD. 14 studies were included in the analysis with a total number of 398 patients. The mean/median LCI ranged from 7.98 to 11.8, whereas mean/median forced expiratory volume in 1 s (FEV1) z-score ranged from −1.98 to −0.5. The LCI was abnormally increased in all studies, whereas only two studies had abnormally decreased FEV1. The LCI also had a stronger correlation with chest computed tomography and magnetic resonance imaging results, compared to FEV1. In conclusion, this review shows that the LCI is abnormally high in PCD from the preschool age up to adulthood. MBW appears to be more sensitive than spirometry in identifying pulmonary function impairment at the early stages of disease. These findings support the use of the LCI in daily clinical practice and provide evidence of using it as an outcome measure in upcoming clinical trials for patients with PCD.